Coworking Spaces as Hubs of Resilience and Support for Ukrainian Entrepreneurs During the War - Ostapenko, Natalia (2024)
Remote work has become very popular all over the world. Nevertheless, the military conflict in Ukraine has affected entrepreneurs in a new way. This dissertation focuses on the role of coworking spaces as centers of support and sustainability for Ukrainian entrepreneurs during the war. The paper explores how coworking spaces adapted to the war conditions, what assistance they provided to the surrounding community and a list of changes that occurred during the war. Qualitative research using semi-structured interviews was used to achieve the objectives. The study involved 8 coworking owners and the founder of Coworking Association of Ukraine. This study showed the high adaptability of coworking centers in Ukraine during the war. With a drop in the number of clients due to mobilization and relocation, coworking centers introduced flexible rates (hourly, daily) to survive. Despite increased security costs (bomb shelters, generators), they became support centers, offering free places to victims and helping volunteers.